2021
DOI: 10.1093/brain/awab390
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 4E-BP1 in juvenile mice alleviates mTOR-induced neuronal dysfunction and epilepsy

Abstract: Hyperactivation of the mechanistic target of rapamycin (mTOR) pathway during fetal neurodevelopment alters neuron structure and function, leading to focal malformation of cortical development (FMCD) and intractable epilepsy. Recent evidence suggests a role for dysregulated cap-dependent translation downstream of mTOR in the formation of FMCD and seizures. However, it is unknown whether modifying translation once the developmental pathologies are established can reverse neuronal abnormalities and seizures. Addr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 92 publications
3
19
0
Order By: Relevance
“…Investigating the molecular pathogenesis of FCD, researchers have shown that aberrant hyperactivation of mTOR kinase disrupts autophagy‐mediated ciliogenesis and induces translational dysregulation, thereby resulting in cortical dyslamination and intractable epilepsy, respectively 47–51 . Also, a small number of mutation‐carrying neurons (e.g., 1% of mutated neurons) in the cortex has been found to be sufficient to induce focal epileptogenesis via noncell autonomous mechanisms 52 .…”
Section: Intractable Focal Epilepsiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating the molecular pathogenesis of FCD, researchers have shown that aberrant hyperactivation of mTOR kinase disrupts autophagy‐mediated ciliogenesis and induces translational dysregulation, thereby resulting in cortical dyslamination and intractable epilepsy, respectively 47–51 . Also, a small number of mutation‐carrying neurons (e.g., 1% of mutated neurons) in the cortex has been found to be sufficient to induce focal epileptogenesis via noncell autonomous mechanisms 52 .…”
Section: Intractable Focal Epilepsiesmentioning
confidence: 99%
“…36,[45][46][47] Investigating the molecular pathogenesis of FCD, researchers have shown that aberrant hyperactivation of mTOR kinase disrupts autophagy-mediated ciliogenesis and induces translational dysregulation, thereby resulting in cortical dyslamination and intractable epilepsy, respectively. [47][48][49][50][51] Also, a small number of mutation-carrying neurons (e.g., 1% of mutated neurons) in the cortex has been found to be sufficient to induce focal epileptogenesis via noncell autonomous mechanisms. 52 Currently, efforts are underway to translate the findings of somatic mutations in FCD into genetic diagnosis and novel therapeutics for FCD patients, including an update to integrated FCD classification with genotyping, 44 detection of low-level somatic mutations in patient's cerebrospinal fluid, 53,54 and a clinical trial of an mTOR inhibitor in FCD type II patients (ClinicalTrials.gov: NCT03198949).…”
Section: Intractable Focal Epilepsiesmentioning
confidence: 99%
“…However, when and where the brain abnormalities emerge and where changes in the brain fit on the pathway from molecular dysfunction need further investigation. It is essential since early intervention before patients present with symptoms might reverse neuronal abnormalities and seizures (Zhang et al, 2020 ; Nguyen et al, 2021 ). most sporadic focal epilepsies, the underlying mechanisms are unclear.…”
Section: Current Knowledge Of Genetic Influence On Brain Network In E...mentioning
confidence: 99%
“…The mammalian target of the rapamycin signaling (mTOR), as the key regulator of protein synthesis and autophagy, plays critical roles in neurophysiological processes such as neural development and brain circuit formation, as well as the continuum of neurological disorders (7)(8)(9)(10)(11)(12). Recently, dysregulation of mTOR signaling has been implicated in infection and inflammatory progresses and acts as an intriguing component of the complex mechanism involved in epileptic neuroinflammation (9,13).…”
Section: Introductionmentioning
confidence: 99%